Prevalence and Prognostic Importance of High Fibrosis-4 Index in COVID-19 Patients. (4th May 2022) - Demir, Nurhan; Yüzbasıoglu, Bilgehan; Calhan, Turan; Ozturk, Savas
Abstract : Introduction . The fibrosis 4 (FIB-4) index was developed to predict advanced fibrosis in patients with liver disease. We aimed to evaluate the association of FIB-4 with risk factors for progression to critical illness in middle-aged patients hospitalized for coronavirus disease 2019 (COVID-19). Method . We included patients aged 35–65 years who were hospitalized following a positive RT-PCR SARS-Cov-2 test in a tertiary hospital. All data were obtained from the medical records of the patients during the first admission to the hospital. The FIB-4 index was calculated according to the equation (age (years) x AST (IU/L)/platelet count (10 9 /L)/√ALT (IU/L)). The FIB-4 index was divided into three categories according to the score categorisation: <1.3 = low risk, 1.3–2.67 = moderate risk, and >2.67 = high risk. Results . A total of 619 confirmed COVID-19 patients (mean age = 52 yrs.) were included in this study; 37 (6.0%) were admitted to the intensive care unit (ICU), of which 44% were intubated and eight (1.3%) patients died during follow-up. The results of patients with high FIB-4 scores were compared with those with low FIB-4 scores. In patients with high FIB-4 scores, male gender, and advanced age, decreased neutrophil, lymphocyte, thrombocyte, and albumin counts, elevated AST, LDH, CK, ferritin, CRP, and D-dimer, and low GFR were the high-risk factors for critical illness. Additionally, the number of patients referred to ICU with high FIB-4 who died had higher scores than from those with low scores. Conclusion . The FIB-4 index derived from baseline data obtained during hospitalisation can be used as a simple, inexpensive, and straightforward indicator to predict ICU requirement and/or death in middle-aged hospitalized COVID-19 patients.